Epidemiological analysis of Bongkrekic Acid poisoning due to contamination of nonfermented rice noodle products in Guangdong Province from 2018 to 2020 - CHEN Zihui; HUANG Rui; LIANG Junhua; WEN Jian; ZHANG Yonghui (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo analyze the epidemiological characteristics of Bongkrekic Acid poisoning due to contamination of nonfermented rice noodle products in Guangdong Province, and provide the scientific basis for the prevention and control of Bongkrekic Acid poisoning.MethodsEpidemiological characteristics of Bongkrekic Acid poisoning in Guangdong Province were analyzed using descriptive epidemiological method.ResultA total of 5 Bongkrekic Acid poisoning events due to contamination of nonfermented rice noodle products were reported in Guangdong Province, including 21 cases and 9 deaths. The case fatality was 42.9%. The major clinical manifestation included vomiting, diarrhea and abdominal pain. The Bongkrekic Acid poisoning events mainly occurred during the third and fourth quarters. The food products involved in the 5 events were wet starch products or wet rice products mass-produced by food processing plants. Different from traditional nonfermented rice noodle products in Guangdong Province, these involved food products were added with a large amount of starch, using sodium dehydroacetate, and stored at room temperature for more than 24 hours, but there was no noticeable spoilage.ConclusionThe 5 nonfermented rice noodle products poisoning events were rare Bongkrekic Acid poisoning events caused by processed foods. It is urgent to further analyze the corresponding potential risks in the production and operation of nonfermented rice noodle products, as well as propose the targeted control measures. At the same time, the food safety education should be strengthened. Wet rice noodles and wet starch products should be stored in cold storage and should be sold or consumed within the shelf life.